The thermoelectric properties of one dimensional Graphdiyne nanoribbons under different stress regulations - Shiyue Li; Yi Zou; Lulu Sun; Ji Ma (Scientific Reports)
Abstract This paper theoretically investigates the thermoelectric properties of armchair-type graphdiyne nanoribbons (2-AGDYNR) and zigzag-type graphdiyne nanoribbons (2-ZGDYNR) under different stress conditions, using the nonequilibrium Green’s function method. Specifically, it explores variations in their energy bands, carrier concentrations, electrical conductivity (σ), thermal conductivity (κ), and thermoelectric figure of merit (ZT). The results reveal that, at the same temperature, the lattice thermal conductivity of 2-ZGDYNR is much lower than that of 2-AGDYNR, emphasizing the anisotropic thermal conductivity characteristics of graphdiyne nanoribbons. The zigzag-type 2-ZGDYNR benefits due to a high power factor and low thermal conductivity, leading to a significantly higher ZT value compared to the armchair-type graphdiyne nanoribbons of the same width. When axial stress is applied at – 1.5 GPa, 2-ZGDYNR achieves its highest thermoelectric conversion efficiency, with a ZT value of 1.115. This study provides a theoretical basis for the application of graphdiyne nanoribbons, with stress applied along their infinite extension, in the field of thermoelectricity.